Implementation of the Policy for Enhancing the Capability of Government Internal Supervisory Apparatus (APIP) at the Ministry of Population and Family Development/BKKBN - Richa Haryanti; Pardamean Daulay; Sait Abdullah (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the implementation of the Government Internal Supervisory Apparatus (APIP) capability enhancement policy at the Ministry of Population and Family Development/National Population and Family Planning Board (Kemendukbangga/BKKBN) under BPKP Regulation No. 6 of 2025. A qualitative approach was employed using interviews, observations, and document reviews. The analysis was guided by George C. Edward III’s policy implementation framework, encompassing communication, resources, disposition, and bureaucratic structure. The findings indicate that policy implementation has generally followed the intended policy direction but has not yet achieved optimal results. Key challenges include limited policy dissemination, inadequate human and financial resources, insufficient supporting facilities, the absence of technical delegation of authority, and the lack of operational standard operating procedures. Conversely, positive commitment from APIP personnel, alignment between national and organizational policies, and the compatibility of APIP functions with policy objectives have supported implementation. This study further demonstrates that APIP capability enhancement is shaped not only by communication, resources, disposition, and bureaucratic structure, but also by the external strategic environment. Accordingly, it proposes an enhanced policy implementation model that extends George C. Edwards III’s framework by integrating empirical evidence from Kemendukbangga/BKKBN and incorporating the external strategic environment as an additional determinant of successful APIP capability enhancement policy implementation.